Efisiensi dan Profitabilitas: Pengujian Peran Komisaris Independen - Ramadona Simbolon (Balance : Jurnal Akuntansi dan Manajemen, 2024)
This study aims to analyze the effect of the Operating Expense Ratio to Operating Income (BOPO) on Return on Equity (ROE) and to examine the role of Independent Commissioners (KOMID) as a moderating variable. The population in this study consists of all companies within the BUMN Holding in Indonesia, which includes parent companies and subsidiaries designated by the Ministry of BUMN. The sample was determined using the purposive sampling method, resulting in 49 BUMN Holding companies that met the predetermined criteria, representing various industrial sectors within the BUMN holding, such as energy, finance, construction, and transportation. The research results reveal that BOPO and KOMID do not have a significant impact on ROE, and KOMID does not act as a moderator in that relationship. Reforms in the governance of state-owned enterprises (BUMN) and the substantial strengthening of the role of independent commissioners, not just quantitatively, are key to driving improvements in financial performance in the future.